Kto jest ofiarą, a kto jest bestią? O przewartościowaniu pojęć "humanitas" i "animalitas" w "Nakarmić wilki" i "Requiem dla wilka" Marii Nurowskiej = Who is the victim and who is the beast? On the reevaluation of the concepts of "humanitas" and "animalitas" in "Feed the Wolves" and "Requiem for a Wolf" by Maria Nurowska - Naplocha, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the reevaluation of the notions of "animalitas" and "humanitas" in Maria Nurowska`s diptych - "Feed the Wolves" and "Requiem for a Wolf". Based on the methodology of animal studies, the relationship of characters?wolf and the relationship between the characters were characterized. Next, the examples of noticeable change in axiological marking of the concepts of "animality" and "humanity" are listed: from objectification to the empowerment of animals and the dehumanization (objectification) of people in the context of therianthropy.
Keywords: dehumanizacja; upodmiotowienie; powieść; aksjologia; Nurowska, Maria (1944-2022); dehumanization; empowerment; novel; axiology